CHILDREN'S STORY OF REALISTIC FICTION AS STRENGTHENING THE VALUE OF THE NATION'S CHARACTER EDUCATIONAL ATTITUDE - Encil Puspitoningrum (Suluh Adiluhung Publisher (SAPub), 2024)
Stories specifically for children are called children's story. The content in it is in the form of daily life that a child carries out in his life. One type of children's story is realistic fiction. This type of research uses literature study. Finding various theories, laws, postulates, principles, or ideas that are used to analyze and solve formulated research questions is the focus of this research. The results of this research show that children's story can be used as a guide in strengthening the values ​​of national character education. Because instilling the values ​​of national character education through children's story is considered capable of helping the formation of students as human beings who have moral and ethical values.